Image analysis: 68Ga-FAPI-46 PET derived texture parameters improve the differentiation of malignant and benign pulmonary lesions - Wessendorf, Joel; Spektor, Anna-Maria; Aboulmaouahib, Brahim; Daum, Johanna; Glatting, Frederik M.; Schlamp, Kai; Grott, Matthias; Eichhorn, Florian; Heußel, Claus Peter; Kauczor, Hans-Ulrich; Kreuter, Michael; Schreckenberger, Mathias; et al. (Cancer imaging, 2025)
Pulmonary lesions inconclusive in 18F-FDG PET/CT are a known clinical problem. Both texture analysis and 68Ga-FAPI-46 have shown potential in thoracic oncological problems but their combination has not been assessed yet. This initial analysis aims to evaluate the utility of 68Ga-FAPI-46 PET texture parameters to differentiate between lung cancer and benign pulmonary lesions inconclusive in 18F-FDG PET/CT.